1993
DOI: 10.1093/jnci/85.13.1038
|View full text |Cite
|
Sign up to set email alerts
|

Tea and Cancer

Abstract: Tea is one of the most popular beverages consumed worldwide. The relationship between tea consumption and human cancer incidence is an important concern. This topic has been studied in different populations by many investigators, but no clear-cut conclusion can be drawn. Whereas some studies have shown a protective effect of tea consumption against certain types of cancers, other studies have indicated an opposite effect. Our purpose is to provide a critical review of this topic, covering basic chemistry and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
561
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 970 publications
(576 citation statements)
references
References 0 publications
10
561
0
5
Order By: Relevance
“…16,17,27 The cancer chemopreventive action of tea has been attributed to its major phytopolyphenols. The tea polyphenols comprise about one-third of the weight of the dried leaf, and they show profound biochemical activities including antioxidant activities, 28 modulation of carcinogen metabolism, inhibition of cell proliferation, 20 induction of cell apoptosis 29 and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,27 The cancer chemopreventive action of tea has been attributed to its major phytopolyphenols. The tea polyphenols comprise about one-third of the weight of the dried leaf, and they show profound biochemical activities including antioxidant activities, 28 modulation of carcinogen metabolism, inhibition of cell proliferation, 20 induction of cell apoptosis 29 and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the results have been reviewed previously [1][2][3][4][5][6][7][8]. Table 1 summarizes the results of 120 studies published since the year 1991.…”
Section: Inhibition Of Tumorigenesis In Animal Models and Possible Mementioning
confidence: 99%
“…In 1991, the Working Group of the International Agency for Research on Cancer (IARC) reviewed the effects of tea on cancers of different sites and concluded that "there is inadequate evidence for the carcinogenicity in human and experimental animals of tea drinking" [58]. In 1993, Yang and Wang reviewed more than 100 published papers and paid more attention to the possible cancer preventive effects of tea consumption [1]. This review summarized that, while some studies showed a negative association between tea consumption and cancer risk, others showed no association or positive association.…”
Section: Studies On Tea and Human Cancermentioning
confidence: 99%
“…Elle procure également des effets bénéfiques chez des rats soumis à un régime riche en lipides en diminuant la masse corporelle, la pression artérielle et les pathologies cardiovasculaires [39]. Le thé possède aussi une grande quantité de polyphénols qui auraient des effets protecteurs contre certains cancers [40] et contre le développement de maladies cardiovasculaires [41]. Parallèlement, un analogue du sucre est à l'étude, le 2-déoxyglucose, qui agit comme un inhibiteur glycolytique.…”
Section: La Restriction Calorique Et Ses Limites Vers Quelles Solutiunclassified